Kansas bull test 15-year summary - Schalles, R.R.; Zoellner, K.O.; Olson, W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Bulls placed in Kansas Bull Tests have increased in weight, gain, frame, and scrotal circumference, while decreasing in fat thickness over the past 15 years. Bull buyers have been willing to pay for increased performance, with changes in bull prices generally reflecting changes in the other cattle prices.
Keywords: Beef; Weight; Gain; Frame; Scrotal circumference; Performance